‘Count your Blessings!’ The Interpretive Potential of Sacramental Theology for Everyday Ritualizations around Food - Mirella Klomp; Peter-Ben Smit (Yearbook for Ritual and Liturgical Studies, 2023)
In this article, the authors explore the yield of a sacramental lens on extra-ecclesial ritualizations around food in contemporary Dutch ‘secularized’ culture. In an effort to explore the scope of sacramental theology beyond the liturgical ritual of the Eucharist/Holy Communion, they conclude that sacramental theology as a heuristic lens has a promising potential to reveal what is at stake when it comes to ordinary practices of food. Taking Louis-Marie Chauvet’s ground-breaking study Symbol and Sacrament as a point of departure for a sacramental frame, and using three examples from a recent Dutch TV series on counting blessings at dinner time, they seek to answer the question “What is the heuristic potential of a sacramental perspective on food-related ritualizations in everyday life?” The authors conclude that everyday ritualizations, in turn, constructively challenge ‘classic’ sacramental and liturgical theology. Thus, a sacramental lens on extra-ecclesial food-related ritualizations can enhance the understanding of the Eucharist/Holy Communion, as well as reveal what is at stake when it comes to ordinary (ritualized) practices of food.